A Novel Approach to Architectural Problem Space Framing Using TRIZ- Based Contradiction Approach. (2015) - Najari, Amirabbas; Barth, Marc; Sonntag, Michel
Abstract: In the absence of a specific form for representation, architectural contradictions are often ignored or treated by intuition, trial-and-error, or compromise. But, the set of methods and tools of Theory of Inventive Problem Solving (TRIZ) would formulate, represent and solve these contradictions. This paper presents a part of an empirical study aimed to explore the possibility of adapting the "Contradiction" concept of TRIZ as a conceptual strategy for the early stages of an architectural design process. To obtain this objective, the architectural program of Project of Extension of INSA de Strasbourg was built in the form of Problems Graph of IDM-TRIZ (Inventive Design Method). This modeling aims to study the possibility of using the information provided by an architectural program to state architectural problems as Contradiction, and its contribution to the understanding of the problem space. Some limitations of the IDM-TRIZ for architectural applications are reported as well, and certain possible developments for Analysis of Initial Situation phase to fit better to the architectural programming process are suggested.